2020
DOI: 10.3390/ijms21072365
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Role of IL-1β Signaling in Chondrocytes Associated with Retinoid Signaling during Fracture Healing

Abstract: The process of fracture healing consists of an inflammatory reaction and cartilage and bone tissue reconstruction. The inflammatory cytokine interleukin-1β (IL-1β) signal is an important major factor in fracture healing, whereas its relevance to retinoid receptor (an RAR inverse agonist, which promotes endochondral bone formation) remains unclear. Herein, we investigated the expressions of IL-1β and retinoic acid receptor gamma (RARγ) in a rat fracture model and the effects of IL-1β in the presence of one of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In addition, several studies have already proven the beneficial effects of retinol on the immune and therapeutic systems [ 28 ]. In addition, the cell proliferative effect of retinol was substantially proven in several studies performed with stem cells [ 29 ], fibroblasts [ 30 ], chondrocytes [ 31 ], keratinocytes, and bone cells [ 32 , 33 ]. Recently, the use of retinol in biomedical applications is an increasing trend, and several novel approaches have been initiated to better use and overcome the major drawbacks of retinol in the practical field.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have already proven the beneficial effects of retinol on the immune and therapeutic systems [ 28 ]. In addition, the cell proliferative effect of retinol was substantially proven in several studies performed with stem cells [ 29 ], fibroblasts [ 30 ], chondrocytes [ 31 ], keratinocytes, and bone cells [ 32 , 33 ]. Recently, the use of retinol in biomedical applications is an increasing trend, and several novel approaches have been initiated to better use and overcome the major drawbacks of retinol in the practical field.…”
Section: Introductionmentioning
confidence: 99%
“…The role of IL-1ß merits further discussion; it appears to have variable effects depending on the cell type, cytokine concentration, and duration of exposure. While some research indicates IL-1ß may encourage chondrocyte proliferation [42], others suggest it can signal programmed cell death [43]. The complexities of IL-1ß's impact on chondrocytes suggest it is modulated by various factors, including the local environment, cytokine levels, tissue health, and the presence of other inflammatory or healing agents [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown in vitro that CCN2 induces chondrocyte proliferation and differentiation, with increased synthesis of cartilage matrix proteins, including proteoglycans, ACAN and collagen types II and X ( Shimo et al, 2000 ; Fujisawa et al, 2008 ). Subsequently, it was found that CCN2 plays a role in chondrogenesis during fractured bone healing; CCN2 expression in this process responds to MAPK and retinoid receptor gamma signalling pathways ( Shimo et al, 2019 , 2005 , 2020 ; Nakata et al, 2002 ; Yosimichi et al, 2006 ). CCN2 expression is highly regulated by TGFβ ( Song et al, 2007 ), with its promoter transcriptional activity maintained by a TGFβ response element ( Eguchi et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%